CENTRO ESPECIALIZADO EN EL TRATAMIENTO A PERSONAS CON CONSUMO PROBLEMÁTICO DE ALCOHOL Y OTRAS DROGAS (CETAD) EN LA CIUDAD DE GUAYAQUIL. - Mosquera Ortiz, Emily. (2022)
Currently, given the evident gap between the need for services for the treatment of people with addictions and their effective provision, as well as the lack of knowledge and awareness that exists, this project is to assign and integrate the city of Guayaquil a Specialized Center for the Treatment of People with Problematic Consumption of Alcohol and Other Drugs located in Puerto Santa Ana. Providing an integrated and functional development for the welfare of each patient welcomed. This project was analyzed through the use of interviews, taking as a refer ence their personal opinions. This preferential location was designated which will have a mixed approach that will allow to promote different modes of interactivity; developing strategies such as social areas that welcome the users of the center to perform new activities, which induce to improve education linking a cognitive development under normative and legal parameters where it will allow to consolidate the architectural design, such as universal accessibility and flexibility with a unique essence to govern the project.